(untitled) (Research, Society and Development, 2020)
Objective: this study aimed to verify the importance of fungal culture in the conclusive diagnosis of dermatophytosis in dogs and cats, given the variability of dermatological signs and their infectious and contagious nature, which can affect humans. Method: retrospective documentary analysis was carried out at the Veterinary Hospital of the Federal University of Jataí, between 2018 and 2019, of the cases in which dermatozoonosis was listed among the clinical suspicions. Fungal culture was carried out in laminoculture with TMD, by means of deposition in the culture medium of scales and broken hair from various suspect sites. After incubation at room temperature, an inspection was carried out to detect the color change from medium to red and colonies growth, followed by morphological identification of macroconids to determine the species. Results: among the 193 dogs treated at the dermatology service, 60 (31.1%) had dermatological signs that justified the inclusion of dermatophytosis among the differential diagnoses. In 43 cats, in 17 (39.5%), dermatophytosis was identified among the possible suspicions. However, after fungal culture, dermatophytosis was confirmed only in 5.7% (11/193) of the total cases treated. In dogs it represented 2.6% and in cats 14% of diagnosed skin diseases. Conclusion: dermatophytosis is often included in the differential diagnosis of skin diseases that develop with alopecic, scaly and crusted lesions. Fungal culture is a fundamental tool for confirming infection and implementing assertive therapeutic measures. M. canis is the most frequent dermatophyte in dogs and cats, which reinforces the need for an accurate diagnosis, due to its zoonotic character.